Variable FZD7 expression in colorectal cancers indicates regulation by the tumour microenvironment - Vincan, Elizabeth; Flanagan, D.; Pouliot, N.; Brabletz, T.; Spaderna, S. (2010)
Recent evidence shows that a sub-population of Wnt/ß-catenin target genes is specifically induced in different tissue contexts. FZD7 is a putative Wnt/ß-catenin target gene and although it is highly expressed in well-differentiated colorectal cancer tumour cells, its expression is decreased in de-differentiated tumour cells at the invasive front despite elevated Wnt/ß-catenin signalling in this area. This variable expression of FZD7 implicates additional regulation by the microenvironment; however, this has not been investigated. To begin to elucidate the role of extracellular matrix in regulating FZD7 expression, we generated a FZD7 promoter reporter and analysed FZD7 promoter activity in colorectal cancer cells grown on different matrices. We demonstrate that the FZD7 promoter is regulated by ß-catenin in colorectal cancer cells and observed decreased promoter activity in cells grown on fibronectin but not collagen I or collagen IV. Thus, expression of FZD7 in colorectal cancer may be regulated by fibronectin in the microenvironment. © 2009 Wiley-Liss, Inc.